Utilization of Digital Comics in Improving Mathematics Learning Outcomes - Mastiah, Sri; Novita, Rita; Putra, Mulia; Syarfuni, Syarfuni; Sitorus, Jonni (Pascasarjana UM, 2024)
Student completeness in learning mathematics is still low and interest in learning is relatively low, because the learning media is less varied and less interesting, and there are still students who have not achieved learning outcomes above the minimum completeness criteria. The purpose of this study was to analyze the use of digital comics in improving mathematics learning outcomes. The research approach used is qualitative and the type of research used is a literature study or literature review. The stages used in this literature study research design include the focus of scientific articles, data collection, data analysis, and conclusions. Based on the results of the literature review, it shows that technology-based innovative media such as comics are learning resources sourced from objects close to students, so that students feel familiar with the media used during the learning process. Technology-based innovative media such as digital comics can increase interest in learning mathematics, by involving students' real experiences. Learning that interests students is influenced by teacher creativity. Utilization of comic media in learning mathematics can improve students' learning outcomes, through the senses of students can observe and listen to the teacher's explanation properly as exemplified by the role in comic media as digital media.